XIAP as a ubiquitin ligase in cellular signaling - Galbán, S; Duckett, C S (Cell death and differentiation, 2010)
The ability of the vertebrate X-linked inhibitor of apoptosis (XIAP) protein to directly suppress apoptotic cell death pathways has been the subject of much research. Studies of this broadly expressed protein have largely focused on the unique interactions between XIAP and caspases – proteases that conduct and participate in the ordered disassembly of the cell during apoptosis. However, relatively less attention has been given to the RING domain of XIAP, which functions as an E3 ligase to catalyze the ubiquitination of substrate proteins. Here, we discuss the evidence implicating the RING domain of XIAP in the ubiquitin-mediated regulation of three, somewhat arbitrarily divided, categories of substrate: XIAP itself, XIAP-interacting proteins involved in apoptosis, and other targets whose physiological roles likely extend beyond cell death. Collectively, these multiple activities of XIAP show that this enigmatic protein participates in a range of cellular activities beyond apoptotic suppression.